Reading the Future? Late Modern Histories of the Fin De Siècle - Hearn, Mark (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
Late modern histories of the fin de siècle have projected present dilemmas and their premonitions of the future into historical analysis. Recent historiographical focus on the global nature of the fin de siècle has also reframed interpretations, both complicating and enriching the history of the period and its relationship with present future. This article explores how historians have in recent decades returned to the fin de siècle and the aspirations of its actors, grappling with the dilemma of reviving progressive ideals and politics in the early twenty-first century through their analysis of the creative and at times contradictory turbulence at work in the late nineteenth and early twentieth centuries.